2011
DOI: 10.1186/1471-2180-11-224
|View full text |Cite
|
Sign up to set email alerts
|

Genome organization of epidemic Acinetobacter baumannii strains

Abstract: BackgroundAcinetobacter baumannii is an opportunistic pathogen responsible for hospital-acquired infections. A. baumannii epidemics described world-wide were caused by few genotypic clusters of strains. The occurrence of epidemics caused by multi-drug resistant strains assigned to novel genotypes have been reported over the last few years.ResultsIn the present study, we compared whole genome sequences of three A. baumannii strains assigned to genotypes ST2, ST25 and ST78, representative of the most frequent ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
92
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(96 citation statements)
references
References 65 publications
3
92
1
Order By: Relevance
“…The majority of mutations in the dinB::Km strain were transversions (7 out of 10), as were the majority of mutations in the dinB ϩ strain (21 out of 32). Analysis of the total sequences of the dinB ϩ and dinB::Km strains combined revealed the majority (67%; 28 out of 42) of base-pair substitutions to be transversions (Table 3), a signature of DNA Pol V in E. coli, and all but one listed substitution (A-to-G transition) are also known to be DNA Pol V generated (45). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of mutations in the dinB::Km strain were transversions (7 out of 10), as were the majority of mutations in the dinB ϩ strain (21 out of 32). Analysis of the total sequences of the dinB ϩ and dinB::Km strains combined revealed the majority (67%; 28 out of 42) of base-pair substitutions to be transversions (Table 3), a signature of DNA Pol V in E. coli, and all but one listed substitution (A-to-G transition) are also known to be DNA Pol V generated (45). …”
Section: Resultsmentioning
confidence: 99%
“…baumannii is notorious for readily incorporating foreign DNA, such as transposons, insertion sequence elements, and antibiotic resistance-encoding islands, into its genome (1,2,45). Therefore, it has the ability to acquire antibiotic resistances possibly from a wide range of bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Internationally, there are several epidemic clonal complexes of A. baumannii (e.g., the international clones I, II, and III) spreading across different health care facilities, and each clonal complex contains a subset of diversified strains (14)(15)(16). Compar-ative genomic analysis revealed that A. baumannii outbreaks at hospitals might be polyclonal and provided evidence for gene transfer and genome reorganization among different frequent genotypes (17)(18)(19)(20)(21). Understanding the genome diversification within a subset of closely related strains from the same clonal complex and their population dynamics during colonization provides insight for evolution and adaptation of bacterial pathogens (22,23).…”
mentioning
confidence: 99%
“…Strains display striking variability in accessory gene content (5,8), including antibiotic resistance genes (9), even among related isolates of a single outbreak (10). This genomic variability presumably reflects the actions of transmissible plasmids, insertion elements, phage, integrons, natural transformation, and recombination (11)(12)(13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 99%